Niebo jako przestrzeń poznana - filmowa interpretacja książki "Niebo istnieje... Naprawdę" = Heaven as a familiar space ? a film interpretation of the novel "Heaven Is for Real" - Kokorniak, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"Heaven Is for Real" is a film interpretation of a novel under the same title. It is a story of a four-yearold boy named Colton, who gives an account of his journey to Heaven. His language is amazinglyeasy and a little bit infantile. Young Burpo depicts details which describe Heaven as a space. He alsotalks about his meetings and conversations with Christ and the dead members of his family. Themost significant role in the movie is played by his father, Todd, who accepts his son?s stories but hassome doubts.
Keywords: adaptacja filmowa